WEB DESIGNING FOR SECOND-HAND CARS PROMOTION AND SALE ON AUTOCAR SHOWROOM USING PHP, MYSQL, AND MACROMEDIA DREAMWEAVER 8.0 - Angga Dika Saputra; Eriek Orlando (Jurnal Sistem Informasi, 2010)
Along with the rapid development in information technology make every persongetting information easier. Internet is a fast and easy way to convey thatinformation reach the wider community. The use of website is very useful forpromoting, offering and informing the sales of cars for the Autocar Showroomsconsumers. The information is presented in a web page display that is easilyunderstood by consumers, start from the main menu to the specific searching ofcars based on brand, type and price of the car. Macromedia Dreamweaver 8.0,PHP and MySQL are a few examples of the many software tools that can solvethe problem.